(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In the rapidly evolving world of digital technology, we are confronted with a huge amount of information on the internet that affects and affects all areas of human activity. This has led to a sharp increase in demand for Web design professionals who can provide easy access to internet resources for internet users. In this regard, one of the most pressing issues today is to think about the quality and challenges of training specialists in this field, to develop solutions to existing problems.